1994
DOI: 10.2166/wst.1994.0354
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incomplete Denitrification on Anoxic-Aerobic (Low F/M) Filament Bulking in Nutrient Removal Activated Sludge Systems

Abstract: Experiments have been performed to investigate the hypothesis that the alternation of anoxic and aerobic conditions is the major factor influencing filamentous bulking in low F/M systems. The results provided strong supporting evidence for the hypothesis; nitrite, rather than nitrate, appears to play a dominant role in causing the bulking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Casey et at. (] 992 and ]994) and Musvoto et at. (1994) have demonstrated that when denitrification in the anoxic reactor preceding the aerobic reactor is incomplete (that is, NO] and N0 2 -leak from the anoxic to aerobic reactors), then the anoxic-aerobic (AA, previously called low-F/M) filaments (for example, M. Parvicella, 0092, 0041, 0675) proliferate to cause bulking with diluted sludge volume indices (DSVls) in excess of 200 mUg; if denitrification is complete, then good sludge settleabilities are obtained with DSVls less than 100 mL/g.…”
Section: Filamentousmentioning
confidence: 98%
See 1 more Smart Citation
“…Casey et at. (] 992 and ]994) and Musvoto et at. (1994) have demonstrated that when denitrification in the anoxic reactor preceding the aerobic reactor is incomplete (that is, NO] and N0 2 -leak from the anoxic to aerobic reactors), then the anoxic-aerobic (AA, previously called low-F/M) filaments (for example, M. Parvicella, 0092, 0041, 0675) proliferate to cause bulking with diluted sludge volume indices (DSVls) in excess of 200 mUg; if denitrification is complete, then good sludge settleabilities are obtained with DSVls less than 100 mL/g.…”
Section: Filamentousmentioning
confidence: 98%
“…In Figure 2 it can be seen that the biodegradable COD comprises two fractions, the RBCOD and the slowly biodegradable COD (SBCOD). Experiments and experience have indicated that for South African wastewaters, the magnitude of BEPR is strongly linked to the influent RBCOD concentration and that thc SBCOD contributes negligibly to the growth of the poly-P organisms and, hence, to the BEPR (Nicholls et at., 1984;Pitman, 1991;and Wentzel et ai., 1994). With regard to the RBCOD, this also has two fractions, SCFAs (also called volatile fatty acids) and the non-SCFAs termed fermentable RBCOD (F-RBCOD).…”
Section: Autotrophs (Nitrifiers)mentioning
confidence: 99%
“…Another possible reason for poor settleablity in the sole methanol addition run can be associated with the degree of denitrification. Casey et al (1992Casey et al ( , 1994 and Musvoto et al (1994) have shown that good sludge settleability was observed with complete denitrification, while filaments proliferate causing sludge bulking with high SVI when denitrification is incomplete. However, more tests related to hydrophicity and filamentous organisms are needed to support the present results clearly.…”
Section: Svimentioning
confidence: 99%
“…Magnesium hydroxide as a new type of water treatment agent has many advantages, such as harmless, easy to pumping and with high adsorption ability. Research shows that: magnesium hydroxide or magnesium salt could remove heavy metals, nitrogen and phosphorus effectively [4][5][6][7]. Comparing to magnesium hydroxide, nano magnesium hydroxide have higher practical value [8][9].…”
Section: Introductionmentioning
confidence: 99%